KNOWLEDGE, ATTITUDE AND PRACTICES OF CONSUMPTION OFCARBONATED BEVERAGES: A CROSS SECTIONAL STUDY - Talha Mufeed Siddiqui et al (Baqai Journal of Health Sciences)
A soft drink or a carbonated drink is a non-alcoholic drink that commonly contains water, a sweetener, carbon dioxide, acidulants, colorings, preservatives, antioxidants, and/or foaming agents, and a flavoring agent. A total of 200 adult patients of low socioeconomic status, aged 18-35 years, were selected to participate in the study. A questionnaire with 26 closed ended questions was designed for the present study which consists of questions regarding knowledge, attitude and practice of consumption of sweetened carbonated beverages. One hundred and ninety nine (99.5%) of the subjects enjoyed drinking soft drinks. Out of 200 subjects only 8 (4%) responded that they will stop drinking soft drinks. The present study results showed that all the target population heard about soft drinks but very few of them were aware of the ill effects on general health and on teeth. So there is a need to spread awareness among people about the adverse effects of the carbonated beverages consumption and thus there is a need to plan health education programs.